Peningkatan Mutu Pelayanan Rekam Medik di RSUD Abdoel Wahab Sjahranie Samarinda - Pangesti .A, Fransiska; Rosarini, Anna; Putradana, Wynne; Audi Agatha, Laurentia; Pratidina Susilo, Astrid (INCOME: Indonesian Journal of Community Service and Engagement, 2023)
The result of data management in hospitals becomes the base of reports and decision-making by the hospital's director, so it should be done quickly and precisely. However, in RSUD Abdoel Wahab Sjahranie Samarinda, problems such as data incompatibility, incompleteness, and lateness still existed. The quality of data in the hospitals is related to the role of medical records. Based on these problems, this activity aimed to find the root of data inaccuracy and lateness in RSUD Abdoel Wahab Sjahranie and to give the recommendation of solutions based on the root of the problems found. This activity was conducted from October 2021 until January 2022. There were three stages of the activity such as preparation, data collection and analysis, and intervention. The root of the problems that were already found was grouped into four topics that are related to the Time of Medical Records' Return, Disease Code in Medical Record Unit and JPKM/case-mix, Data Acquisition and Accuracy, and Daily Census and Patient Recording. Solutions to these problems are to improve the returning Medical Record Sheets' and daily census flow and SOP, and redesign the Daily Census form. These improvements were giving the hospital good results regarding the faster return of medical records and acceleration of BPJS Kesehatan claiming time.